Participation Potential of Rural Women in Different Homestead Farm Activities (The Agriculturists, 2014)
The main purpose of the study was to determine the extent of participation of rural women in the cultivation of vegetables and fruit trees around the homestead areas. The study was conducted on married women of four selected villages of Raumari upazilla under Kurigram district. Data were collected from randomly selected 103 women by using pre-tested interview schedule during the month of May, 2013. In measuring the participation of rural women in homestead farm activities, cultivation of vegetables and fruit trees were considered as dependent variables. Each aspect consisted of 15 activities under three sub-headings. A three point Likert-type scale was used to measure each activity. The independent variables were measured by employing prevailing standard methods. Pearsons correlation coefficient (r) was used in order to explore the relationships between the concerned variables. About 59 percent of the rural women had high participation in vegetables cultivation while only 10.68 percent of them had low participation in the cultivation of fruit trees. Among 15 statements of different aspects in relation to vegetables cultivation, tilling by spade was ranked first. In case of the cultivation of fruit trees, the highest proportion (46.60 percent) of rural women had medium participation and irrigation after planting was in the first position. Agriculture knowledge, attitude and innovativeness had positive relationship with the cultivation of vegetables. On the other hand, education, family income, cosmopoliteness behaviour and attitude had positive relationship with the cultivation of fruit trees. DOI: http://dx.doi.org/10.3329/agric.v12i1.19581 The Agriculturists 2014; 12(1) 57-67